Pengaruh Penggunaan Strategi Pembelajaran Small Group Discussion Terhadap Keaktifan Belajar Siswa Kelas VIII Pada Mata Pelajaran PAI Di SMPN 1 Palupuh - Rizki Andini; Supriadi Supriadi; Fauzan Fauzan; Hamdi Abdul Karim (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
This research is motivated by the low activeness of student learning caused by learning that is still teacher-centered so that students do not actively participate in the learning process such as when the teacher asks questions no one raises their hand to answer the question, students also do not take the initiative to ask when the teacher does not understand what has been conveyed by the teacher, this is also caused by the use of monotonous learning strategies so that students feel bored and bored when learning takes place. The purpose of this research is to find out how much influence the use of Small Group Discussion learning strategies has on activeness study class VIII students at SMPN 1 Palupuh. This research is a Quasi-Experimental Design or quasi-experimental design. The design used is the Nonequivalent Control Group Design using quantitative data trends. The population in this study amounted to 60 people consisting of two classes. The sample for this study was class VIII 1 as the experimental class and class VIII 2 as the control class. The experimental class was given treatment using the Small Group Discussion strategy while the control class was not given treatment. The data analysis technique used was the t test which had previously passed the prerequisite analysis test by carrying out the normality and homogeneity tests. The results showed that there was an effect of using the Small Group Discussion strategy on student learning activity significantly with a significant value of Sig <0.05 (0.000 < 0.05) and t count > t table (7120> 2.001), it can be concluded that is rejected and is accepted.